Indoleamine 2,3-Dioxygenase Immune Status as a Potential Biomarker of Radioiodine Efficacy for Advanced Distant Metastatic Differentiated Thyroid Cancer - Shi, Liang; Duan, Rui; Jia, Qiong; Wu, Wenyu; Zhou, Jianming; Li, Shaohua; Zhang, Hao; Xue, Xue (Frontiers in Oncology, 2022)
Purpose Host immunity influences the impact of cancer therapy but the effect of immune status in radioiodine (RAI)-treated differentiated thyroid cancer (DTC) remains obscure. Here we investigated indoleamine 2,3-dioxygenase (IDO) activity as a biomarker of response to RAI in patients with distant metastatic DTC (dmDTC). Methods Patients with dmDTC receiving RAI were evaluated for serum IDO activity (kynurenine and kynurenine:tryptophan ratio) at baseline and 3 months after RAI. The optimal cut-off value for these biomarkers to predict response was established by receiver operating characteristic analysis. The relationship between disease outcomes, overall survival (OS) and progression-free survival (PFS), and IDO activity levels was studied. Results Higher baseline kynurenine:tryptophan ratio (>2.46) was correlated with poorer RAI response as well as shorter median PFS (45 mo versus not reached, p=0.002) and OS (78 mo versus not reached, p=0.035). High baseline kynurenine:tryptophan ratio was also correlated with a reduced number of tumor-infiltrating lymphocytes. Higher post/pre-kynurenine ratio (>1.69) was associated with survival endpoints: shorter median PFS (48 mo versus not reached, p=0.002) and OS (68 mo versus not reached, p=0.010). Favorable baseline and favorable change corresponded with better PFS and OS. Conclusions Our results suggest that RAI also alters IDO activity in dmDTC patients. IDO activity could predict progression and survival outcomes for advanced dmDTC patients. Serum IDO biomarker levels could be used to select dmDTC likely to benefit from RAI therapy, although further studies are necessary.